1995
DOI: 10.1136/fn.73.3.f147
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory illness in families of preterm infants with chronic lung disease.

Abstract: Aims-To examine the relation, based on two types of questionnaires, between (1) chronic lung disease of the newborn (CLDN) and lower respiratory illness (LRI) in siblings, and between (2) CLDN and asthma, chronic obstruction pulmonary disease (COPD), or allergy in parents and grandparents. Methods-Data from 209 children born before 32 weeks ofgestation were randomly taken from the records of three neonatal units. Taking into account age and gender, the excess of LRI was calculated for each family compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It is therefore better to prevent than to cure RDS because the absence of RDS will result in reduced risks for developing CLDN, 18 even at 36 weeks' postconceptional age. 19 The prophylactic administration of surfactant is a significant factor (P Ͻ .01) in reducing the odds for mortality and severe RDS, and therefore also for CLDN. BW, gestational age, gender, and the prenatal administration of glucocorticosteroids are important confounders.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore better to prevent than to cure RDS because the absence of RDS will result in reduced risks for developing CLDN, 18 even at 36 weeks' postconceptional age. 19 The prophylactic administration of surfactant is a significant factor (P Ͻ .01) in reducing the odds for mortality and severe RDS, and therefore also for CLDN. BW, gestational age, gender, and the prenatal administration of glucocorticosteroids are important confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Data from older studies have suggested a relationship between “old” BPD and first‐ or second‐degree relatives with a history of asthma 14 . However other studies demonstrated no difference in severity of BPD in children and FHA 15,16 or if FHA is associated with an increase risk for respiratory symptoms after NICU discharge.…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, experimental studies in the rat suggest that it may inhibit alveolar development. 49 The effect of other treatments such as surfactant replacement therapy 50 or antioxidant enzymes 51 on lung development and growth are not known.…”
mentioning
confidence: 99%